PERANAN INTERNAL AUDIT DALAM MENGATASI DAN MENGUNGKAPKAN PRAKTEK KECURANGAN PADA PT. BANK MANDIRI Tbk KANWIL I MEDAN - Veby Zoraya Fikri Lubis; Ahmad Prayudi (JURNAL AKUNTANSI DAN BISNIS : Jurnal Program Studi Akuntansi, 2016)
This study aims to determine the role of internal audit in PT. Bank Mandiri Tbk regional office I Medan to express and cope with fraudulent practices. Whether the auditor has an adequate role in articulating and tackle fraudulent practices in PT. Bank Mandiri Tbk regional office I Medan or not. The method used is descriptive method, a method where researchers collect research data and other literature and then expound to know the research problem and find solutions. Data collected by interview, documentation, and distributing questionnaires to 20 employees of the Internal Audit Unit (IAU) PT. Bank Mandiri Tbk regional office I Medan. The questionnaire was tested for validity and reliability by using Cronbach's Alpha method. The results of this study indicate that the internal audit, otherwise known as SPI in SOEs, have an adequate role in articulating and tackle fraudulent practices in PT. Bank Mandiri Tbk regional office I Medan.